The Digital Life of Literature: Hybrid Formats of Text Representation and Role Strategies of a Reader’s Self-Presentation - N. L. Zykhovskaia; D. I. Klopotyuk (Библиосфера)
The problematic of digital representation of the literary process (in all the diversity of structural elements of its representation) is considered as a relevant field of interdisciplinary scientific discourse. The constantly changing digital image of modern literature (thematic groups and fan communities in social networks, electronic libraries, podcasts, blogs, literary Internet shows and other formats that determine its digital landscape), provokes researchers to search for models and concepts that allow us to capture this diversity within the boundaries of scientific reflection. In light of developing theories of convergent culture and intermediality, the concept of hybrid cultural format can be considered as the result of combining heterogeneous environments, forming a holistic and self-sufficient system. The purpose of this study is to understand the specifics of the functioning of literature in new hybrid formats (network representation of literary texts), generated by the digital environment of existence and giving rise to similar – hybrid role strategies of readers. Based on Clifford Geertz’s method of cultural analysis (the “thick description” method) and the methodology of frame scenarios, the authors analyze the resources that actively participate in the creation of the Russian space of digital literary life and represent hybrid models of text functioning. The article builds an identification profile of the reader, expressed through the hybridization of the subject role (creative consumer) and hybrid behavioral scenarios (reader-player). The authors assess the nature of the digital space of literary life as an analogue of carnival culture (M. M. Bakhtin), which gives the modern reader the opportunity to compensate for the illusory nature of virtual existence in the authenticity of cultural-creative action.